Therapeutic venesection at the Australian Red Cross Blood Service: Impact of the High Ferritin Application on management of hereditary haemochromatosis - Bentley, P.; Bell, B.; Olynyk, John (Royal Australian College of General Practitioners, 2015)
© The Royal Australian College of General practitioners 2015. Background Therapeutic venesection is an established treatment for hereditary haemochromatosis. The C282Y homozygotes and C282Y/H63D compound heterozygotes are the most likely human haemochromatosis protein (HFE) variants to cause iron overload. The principal indications for treatment include iron overload, which is detected through measurement of hepatic iron concentration or a liver biopsy, or suspected iron-overload on the basis of elevated serum ferritin levels. Venesection is not indicated for other HFE genetic variants or in patients with isolated hyperferritinaemia in the absence of the main HFE gene mutations. The Australian Red Cross Blood Service provides a therapeutic venesection program. Since January 2013, referral has been conducted electronically using the novel, web-based High Ferritin Application. Objectives The aim of this article is to provide information regarding implementation of the High Ferritin Application and document its impact on referral patterns. Discussion This referral process is based on nationally endorsed, evidencebased algorithms, which have markedly reduced the number of unnecessary therapeutic venesections. An estimated 4000 unnecessary venesections are averted each year and this equates to a saving of $1.4 million.